МОТИВАЦІЯ САМОСТІЙНОЇ НАВЧАЛЬНОЇ ДІЯЛЬНОСТІ СТУДЕНТІВ ВИЩИХ ТЕХНІЧНИХ НАВЧАЛЬНИХ ЗАКЛАДІВ (Педагогіка вищої та середньої школи, 2008)
The main aspects and points of professional motivation of the technical university students’ self-work are determined in this article. The lecturer’s functions within students’ self-work, are de fined.